2012
DOI: 10.1007/s00449-012-0868-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous saccharification and fermentation of broken rice: an enzymatic extrusion liquefaction pretreatment for Chinese rice wine production

Abstract: Broken rice, pretreated by enzymatic extrusion liquefaction, was used to produce Chinese rice wine by simultaneous saccharification and fermentation (SSF) process in this study. The study compared the novel process and traditional process for Chinese rice wine fermentation utilizing broken rice and head rice, respectively. With the optimum extrusion parameters (barrel temperature, 98 °C; moisture content, 42% and amylase concentration, 1‰), 18% (v/v at 20 °C) alcoholic degree, 37.66% fermentation recovery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 24 publications
2
43
2
Order By: Relevance
“…A. Oryzae has strong secretion of amylases including alpha-amylase, which will certainly accelerate the degradation of grains and provide more nutrients for microbes in fermentation. Li, H. et al 27 reported an improvement of rice wine fermentation using grinded grains, suggesting the importance of quick grain degradation in the course of rice wine fermentation. The results here revealed that different microbial makeup greatly influenced the fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…A. Oryzae has strong secretion of amylases including alpha-amylase, which will certainly accelerate the degradation of grains and provide more nutrients for microbes in fermentation. Li, H. et al 27 reported an improvement of rice wine fermentation using grinded grains, suggesting the importance of quick grain degradation in the course of rice wine fermentation. The results here revealed that different microbial makeup greatly influenced the fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the synergy of extrusion shear and enzymatic hydrolysis, which improved the digestion of protein in sticky rice flour, and because of the reduced Maillard reaction in the enzymatic exturdates, which would benefit the reserve of AAs as Maillard reaction substrates. Furthermore, the content of AAs in enzymatic extrusion‐processed rice wine was approximately 2‐fold higher than conventional extrusion‐processed wine (Lu and others ; Li and others ). A possible reason may be the advantage of AA reservation in enzymatic extruded rice.…”
Section: Resultsmentioning
confidence: 92%
“…There are 3 explanations offered: (1) the formation of Maillard‐style volatiles can be inhibited by controlled extrusion conditions at relatively mild levels as described in this study; (2) the release of total volatiles may be enhanced by mild extrusion conditions, especially those lipid‐derived volatiles; (3) the promotion of the reactions between the degradation products of starch, protein, and lipid may be due to the modified reaction environment by increased SME and reduced enzyme activity, which would increase the relative amounts of total volatiles in mildly enzymatic extruded rice. Zhengyu Jin and others (Li and others ) had already demonstrated that the hydrolysis rate of amylopectin increased with thermostable α‐amylase added during enzymatic extrusion, and rice starch was mainly degraded into maltose under low‐temperature operating conditions. Moreover, an optimal product temperature level (94.84 to 96.65 °C) detected for the selected thermostable enzyme at 90 °C also merited attention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations